Russia's Chechen wars 1994-2000 : lessons from urban combat - Oliker, Olga (Rand, 2001)
An examination of the difficulties faced by the Russian military in planning and carrying out urban operations in Chechnya. Russian and rebel military forces fought to control the Chechen city of Grozny in the winters of 1994-1995 and 1999-2000, as well as clashing in smaller towns and villages. The author examines both Russian and rebel tactics and operations in those battles, focusing on how and why the combatants' approaches changed over time. The study concludes that while the Russian military was able to significantly improve its ability to carry out a number of key tasks in the five-year interval between the wars, other important missions--particularly in the urban realm--were ignored, largely in the belief that the urban mission could be avoided. This conscious decision not to prepare for a most stressful battlefield met with devastating results, a lesson the United States would be well served to study.